Hammer and Nails - Bledsoe, Josh; Warrick, Jessica (Brooklyn, NY : Flashlight Press, 2016)
"After her play date is cancelled, a young girl and her dad have a fun day tackling their to-do lists together."--
Keywords: Fathers and daughters -- Juvenile fiction; Play -- Juvenile fiction; Fathers and daughters -- Fiction; Play -- Fiction; JUVENILE FICTION / Family / General (see also headings under Social Issues); JUVENILE FICTION / Family / Parents